DETERMINANTS OF GOING CONCERN AUDIT OPINIONS IN INDONESIAN CONSUMER SERVICE COMPANIES - Gandhy Fitriawansyah; Sofyan Halim (Center for Indonesian Accounting Studies, 2025)
The Study was conducted to examine the influence of Profitability, Debt Ratio, Audit Quality, and the implementation of Good Corporate governance on going concern audit opinion. The research focused on companies within the consumer services sector that are listed on the Indonesia Stock Exchange during the period 2019-2022. The study utilized 100 samples taken from 25 different companies, selected through a purposive sampling technique. A descriptive research method was applied, with logistic regression used as the primary analytical tool. The findings indicate that profitability, debt ratio, and audit quality do not have a significant impact on going concern audit opinion. In contrast, good corporate governance was found to have a significant influence on the opinion. The contribution of this research lies in broadening the understanding of factors affecting going concern audit opinions, thereby enriching theoretical development in the auditing field. From a practical perspective, the results are useful for business practitioners, investors, and policymakers in assessing key factors related to a company's business continuity. Furthermore, the findings can serve as a foundation for formulating policies aimed at enhancing the integrity of capital markets and protecting stakeholder interests, particularly within the consumer services sector.